Network-Based Debugging: Internet Appliances In The Wild - Wong, William (Electronic Design, 2001)
Java has three standards associated with its debugging interface. The first is the Java Virtual Machine (VM) Debug Interface on the Java VM. The second is the Java Debug Wire Protocol used to connect the VM to a debugger. Finally, there's a Java Debug Interface (JDI), which consists of a set of Java classes that allow a Java-based debugger to debug an application running on a Java VM.